Effect of Yoga Practice, Breathing Exercise and Sun Salutation on Body Mass Index for Sports Science Higher Diploma University of Jaffna Students - Ketheeswaran, K. (My University, 2022)
The Purpose of the study is to investigate the Effect of Yoga Practice, Breathing Exercise and Sun Salutation on Body mass Index among Sports Science Higher Diploma Students. The subjects were 30 Sports Science Students. Subjects' age ranged from 19 to 24. The subjects were Part time Students. Before the Yoga Practice, Breathing Exercise and Sun Salutation measured Body Mass Index after 8 weeks Yoga Practice, Breathing Exercise, and Sun Salutation were conducted sirsasana, Sarvangaasana, Halasana, Setubandasana, Matsyasana, Paschimothanasana, Bhujangasana, Salabhasana, Dhanurasana, Ardhamatsyendrasana, Kakasana, Mayoorasana, Padahasthasana, Trikonasana) Sun salutation (it is a warm up exercise that practiced before the stating Asana 12 different spinal positions) Relaxation (Physical Relaxation, Mental & Spiritual Relaxation) Mental benefits include refreshing and invigoration of the mind, creating a feeling of exhilaration, activating pranic energy Applied different breathing exercises include Anuloma viloma (Alternate Breathing), Kapalapathi and Nadi shuti Again same measurement were taken The data was Analyzed by applying Paired t-test and descriptive Statistics technique and Product Measurement Correlation was employed to observed the mean (M) Standard Deviation (SD) and other Parameters. The analysis of data was gained out by using the IBM-SPSS Version 20. The level of Significance was set at 0.05.The findings of the Research study have indicated that Yoga Practice gave Significant reduction on body mass index for Sports Science Higher Diploma, University of Jaffna Students.
Keywords: Asana; Breathing Exercise; Sun Salutation; Relaxation